The game changer how leading organizations in sport and business changed the rules of the game - Gray, Alistair (Routledge, 2019)
The Game Changer powerfully demonstrates how some organisations in business and sport have done more than raise their performance; they have also changed the rules of the game or the game itself within their industry. It gives examples of the strategies and governance programmes that have emerged to accomplish this, and the challenges of executing them. This book brings to life strategic management in business, sport and not-for-profit organisations. It explores many of the theories taught on MBA and other professional programmes through case studies from the worlds of sport and business, written by authors who have played a part in the change. Alistair Gray has spent much of his career in senior roles in these sectors and brings a unique insight to the field, as well as providing the reader with tools and techniques for improvement in governance and performance. The Game Changer is essential reading for both professionals looking for methods to improve their own performance and to embed strong principles of governance, and business students looking for real-life lessons from practice
Keywords: Strategic planning; Management; Organizational change; Sports administration